Critical Human Resource Development on the Relationship Between Quality Work Life and Lecturer Performance Public and Private Universities in Indonesia - Qristin Violinda; Noni Setyorini; chadiyan faturachman; Zhou Deyi (Universitas Negeri Malang, 2024)
The demands of lecturers are getting higher; however, this is not fully accompanied yet with the guarantee of welfare. The research aims to assess the impact of quality work life (QWL) towards the performance of lecturers at Private and State University in Indonesia which mediated by the critical human resources development (CHRD). This study used quantitative approach with partial least square-structural equation modelling. A purposive sampling method was involved with the criteria of the permanent lecturers in the private and state universities in Indonesia. The results indicate that there is no difference between the QWL in private and state universities in Indonesia. While CHRD has significant impact towards performance. Career development, facilities, work load, and work life balance has positive impact towards QWL. The research also shows that QWL has significant positive impact towards performance when it is mediated with CHRD. Thus, there is a need for the state and private universities in increasing the performance by building a working environment that support, invest in employee development, and aligning the human resource strategy with the organization’s goal and also increasing the satisfaction and productivity of the lecturers and staffs. Keywords: Quality of work life, Critical human resource development, Lecturer performance